(untitled) (International Journal of Engineering and Computer Science, 2015)
Palmprint recognition is one of the most important approaches of biometric technology and is one of the most reliable and successful human being identification and authentication methods. In this paper, several existing palmprint recognition algorithms have been studied and analyzed. These palmprint recognition helps to identify the individuals effectively. A simple approach to pre-processing and ROI extraction has been discussed. The available databases have also been analyzed and the most efficient of all will be used for the development of the proposed system. The technique described in this paper gives an overview of palmprint recognition